ANALISIS MINAT MASYARAKAT UNTUK MENABUNG DI BANK SYARIAH INDONESIA CABANG SUMBAWA - S Shulasti; Novi Kadewi Sumbawati (Jurnal Ekonomi & Bisnis, 2025)
This study aims to analyze the determinant of people's interest in saving at Bank Syariah Indonesia Sumbawa Branch, including psychological factors, personal factors and social factors. The type of this study was associative causal. The type of data used was quantitative, in the form of scores of respondents' answers to questions or statements collected directly from respondents using a questionnaire. Respondents who participated in this study numbered 100 people who were determined using the Slovin formula and selected randomly using the simple random sampling method. The collected data will be processed using the SPSS program to be studied using techniques including multiple linear regression analysis, partial parameter hypothesis testing (t-test), simultaneous parameter hypothesis testing (F-test), and coefficient of determination (R2) testing. The results of this study showed that psychological factors, personal factors, and social factors had a positive and significant effect on people's interest in saving at Bank Syariah Indonesia Sumbawa Branch, both partially and simultaneously. The variables of psychological factors, personal factors, and social factors had a significant contrbution on the interest in saving at BSI KC Sumbawa. The ability of the variables of psychological factors, personal factors, and social factors in effecting the interest in saving at BSI KC Sumbawa was 49.4%, while the remaining of 50.6% was effected by other variables outside this study, such as quality service, effective promotions, and strategic location.